DESCRIPTION OF THE NERVE CONDUCTIVE STUDY RESULTS OF PATIENTS WITH DIABETIC POLYNEUROPATHY IN MANADO, INDONESIA - Hugo Dwiputra Wiradarma; Stella; Herlyani Khosama; Seilly Y Jehosua (Jurnal Sinaps, 2020)
Introduction: Diabetic Polyneuropathy (DP) is one of the most frequent complications of diabetes mellitus (DM) which causes high morbidity and mortality. Axonal degeneration is a pathognomonic sign of DP pathophysiology. Nerve conductive study is a common neurophysiologic tool to diagnose DP, however there were no any descriptive study for it in Manado. This study aims to describe the distribution and prevalence of the affected nerve, thus a mapping of the neuropathy in diabetic patients can be obtained. Methods: The data were taken retrospectively by including subjects aged >30 years old who suffer from DM and had complaints of burning sensation, numbness, tingling and prickling in the lower and upper extremities with a symmetrical distribution of gloves and stockings. Subjects with a history of alcohol consumption, thyroid disease, impaired kidney & liver function, heart and adrenal disease were excluded. Nerve conduction study was performed on motor and sensory nerves in both upper and lower extremities. Results: There were 59 subjects included in this study, with nearly identical ratio (men 50.85% & women 49.15%) with a mean age of 56.7 years old (ranging from 34 to 80 years old). All subjects had axonal polyneuropathy (100%) and 27.1% subjects had secondary demyelination. Entrapment abnormalities were most commonly found in the median nerve (57.6%). The most common motor abnormalities were peroneal nerve (81.4%) and sural nerve for sensory abnormalities (98.3%). Discussion: All subjects had axonal disorders and small proportion of patients had secondary demyelination which was caused by metabolic and microvascular complications of diabetes. Entrapments were most commonly found in the median nerve, possibly because of the highest mobility for repetitive movements in hands. All patients exhibited sensorimotor disorders with the greatest abnormalities found in the lower extremities in accordance to length-dependent neuropathy.